Orientations toward Conflict and the Conditional Effects of Political Disagreement. (4th June 2014) - Testa, Paul F.; Hibbing, Matthew V.; Ritchie, Melinda
Abstract : We examine how differences in individual orientations toward conflict condition the effects of disagreement on political tolerance, knowledge, and participation. Past research, while recognizing the importance of individual-level moderators, has focused primarily on conflict aversion as an explanatory factor. Using three surveys, we show that individuals' possess distinct positive and negative orientations toward conflict both of which condition the effects of political disagreement. We find that people who are more positively disposed toward conflict experience more of the benefits and bear less of the costs of political disagreement than those with less positive and more negative dispositions. Possessing a positive orientation toward conflict appears to be a precondition for disagreement to produce higher levels of political tolerance and differences in both positive and negative orientations account for large gaps in both political knowledge and participation.